A two-stage hybrid flow shop problem with dedicated machine and release date - Nabli, Zouhour; Khalfallah, Soulef; Korbaa, Ouajdi (Procedia computer science, 2018)
This paper presents a mathematical model, three heuristics and two lower bounds in order to solve the hybrid flow shop scheduling problem with parallel machines at the first stage and two dedicated machines at the second stage. Each job is subject to a release date at stage one. The objective is to minimize the makespan.